STUDIES ON THE GROWTH OF THE WEDGE CLAM, DONAX (LATONA) CUNEATUS LINNAEUS - Nayar, K Nagappan (Indian Journal of Fisheries, 2016)
OF the several species of wedge clams of the family Donacidce that occur onthe east and west coasts of India in the surf-beaten sands, Donax scortumto some and Donax cuneatus to a very large extent are valued as food bymany people. In the Palk Bay, ail along the beach from Pillaimadam shore